Gender Wage Gap among Young Adults: A Comparison across British Cohorts - Francesca Foliano; Alex Bryson; Heather Joshi; Bożena Wielgoszewska; David Wilkinson (Institute of Labor Economics (IZA), 2023)
We study the evolution of the gender wage gap among young adults in Britain between 1972 and 2015 using data from four British cohorts born in 1946, 1958, 1970 and 1989/90 on early life factors, human capital, family formation and job characteristics. We account for non-random selection of men and women into the labour market and compare the gender wage gap among graduates and non-graduates. The raw and covariate adjusted gender wage gaps at the mean decline over the period among nongraduates, but they rise among young graduates. The gender wage gap across the wage distribution narrows over time for lower wages. Adjusting for positive selection into employment increases the size of the gender wage gap in earlier cohorts, but selection is not apparent in the two most recent cohorts. Thus the rate of convergence in the wages of young men and women is understated when estimates do not adjust for positive selection in earlier cohorts. Differences in traditional human capital variables explain only a very small component of the gender wage gaps among young people in all four cohorts, but occupational gender segregation plays an important role in the later cohorts.
Keywords: J16; J2; J3; 330; gender wage gap; birth cohorts; employment selection; graduates; occupational segregation